Membrane Measurement, Device Simulations of Nanochannel, Nanopore and Nanofluidics Electronics Calculator - Ragulranjith, Senthil Kumar; Vishal, Nandigana V. R. (Transactions on Engineering and Computing Sciences, 2025)
In this article we measure the surface potential of the polycarbonate track etched membrane having multiple nanopores and graphene/copper membrane having multiple nanopores. We use potassium chloride elec trolyte solution (KCl) with 0.6 mol in the high concentration inlet source reservoir. We use 0.6 mmol potassium chloride electrolyte solution in the low concentration outlet sink reservoir. We provide theory to match the surface potential of the membranes. We develop model to understand the potassium ion transference number inside the multiple nanopores for our membranes. We develop GUI simulation to understand the concentration of the potassium chloride electrolyte solution inside single nanochannel, single nanopore for different surface potential of the membranes. We use Gouy-Chapman equation to calculate the concentration and Smolu chowski model is used to calculate the velocity of the potassium chloride electrolyte solution. Here we present a detailed comparative analysis of the structural, transport mechanisms of nanochannels, nanopores to ex plain the several orders of magnitude difference in the current inside the nanochannel and the nanopore. The volume of the single nanochannel is larger than the volume of the single nanopore resulting in larger charge of the potassium ions, chlorine ions and potassium chloride electrolyte solution inside the single nanochannel compared to the single nanopore resulting in the significant difference in the current. We develop GUI based simulation of nanofluidics electronics calculator. Each button of the calculator is related to their own current of the potassium chloride electrolyte solution inside the nanochannel and nanopore, respectively.